If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 4z = 5z + 1 Combine like terms: 2z + 4z = 6z 6z = 5z + 1 Reorder the terms: 6z = 1 + 5z Solving 6z = 1 + 5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-5z' to each side of the equation. 6z + -5z = 1 + 5z + -5z Combine like terms: 6z + -5z = 1z 1z = 1 + 5z + -5z Combine like terms: 5z + -5z = 0 1z = 1 + 0 1z = 1 Divide each side by '1'. z = 1 Simplifying z = 1
| -x^2-5x-18=0 | | 2a-7/5+5=2a | | 5/2y+10x+4=11x | | -3(3)+6= | | 0.504=0.9*w*0.7 | | x-3(1-3)=47-x | | 6a+3b+-8a+5ab+-7b= | | 12x+4x+5=5x+8+3x | | 5.3y+0.5=3.1y-5 | | x+14=20x | | 60=2i+2(14) | | 13=1-7x | | 4.8x+3.1=2.3x+10.1 | | I-12=v | | 55=2y+15 | | 6a+3b-8a+5ab-7b= | | (0.15x+x^2)/(4-4x+x^2) | | 5x-8(x+5)=3-3x | | 139-y=283 | | .45x^2+11.7x=101.4 | | -(2x+4)-x+2-3x= | | x^2+20x=200 | | 4=m+17 | | x^2-20x=200 | | 5(x+5)=32 | | (6k-4)(5k-2)= | | p-45=-20 | | 12x-4=8x+2 | | x+11.3=-5.3 | | (28a+4)/((7a+1)*(7a-1)) | | x^2+13x+28=0 | | 5n+3=24 |